МАРКЕТИНГ ОТНОШЕНИЙ - НОВЫЕ ПЕРСПЕКТИВЫ ДЛЯ РОСТА - Секенова, Д Е; Аликбаева, А Б; Турлыбекова, Н М (Journal of Economic Research & Business Administration, 2015)
In this article author says about new conception of marketing – partnership marketing. There are opened main idea, reason of beginning of conception and prerogatives for companies and clients.